The remarkable diversity of plant PEPC (phosphoenolpyruvate carboxylase): recent insights into the physiological functions and post-translational controls of non-photosynthetic PEPCs - O'Leary, Brendan; Park, Joonho; Plaxton, William C (Biochemical journal, 2011)
PEPC [PEP (phosphoenolpyruvate) carboxylase] is a tightly controlled enzyme located at the core of plant C-metabolism that catalyses the irreversible β-carboxylation of PEP to form oxaloacetate and Pi. The critical role of PEPC in assimilating atmospheric CO(2) during C(4) and Crassulacean acid metabolism photosynthesis has been studied extensively. PEPC also fulfils a broad spectrum of non-photosynthetic functions, particularly the anaplerotic replenishment of tricarboxylic acid cycle intermediates consumed during biosynthesis and nitrogen assimilation. An impressive array of strategies has evolved to co-ordinate in vivo PEPC activity with cellular demands for C(4)-C(6) carboxylic acids. To achieve its diverse roles and complex regulation, PEPC belongs to a small multigene family encoding several closely related PTPCs (plant-type PEPCs), along with a distantly related BTPC (bacterial-type PEPC). PTPC genes encode ~110-kDa polypeptides containing conserved serine-phosphorylation and lysine-mono-ubiquitination sites, and typically exist as homotetrameric Class-1 PEPCs. In contrast, BTPC genes encode larger ~117-kDa polypeptides owing to a unique intrinsically disordered domain that mediates BTPC's tight interaction with co-expressed PTPC subunits. This association results in the formation of unusual ~900-kDa Class-2 PEPC hetero-octameric complexes that are desensitized to allosteric effectors. BTPC is a catalytic and regulatory subunit of Class-2 PEPC that is subject to multi-site regulatory phosphorylation in vivo. The interaction between divergent PEPC polypeptides within Class-2 PEPCs adds another layer of complexity to the evolution, physiological functions and metabolic control of this essential CO(2)-fixing plant enzyme. The present review summarizes exciting developments concerning the functions, post-translational controls and subcellular location of plant PTPC and BTPC isoenzymes.